Coelidinae (Insecta: Hemiptera: Cicadellidae) from Tambopata, Madre de Dios, Peru: checklist with new records and description of a new species of Daridna Walker, 1858 - Barbosa, Julianna Freires; Gonçalves, Clayton Corrêa (Zootaxa, 2021)
A checklist of the coelidine leafhoppers of Reserva Nacional Tambopata, Madre de Dios, Peru, is provided, increasing the known diversity from 19 species and 9 genera, to 38 and 18, respectively. In addition, four species have their distributions expanded and recorded for the first time for Peru: Boliviela caverna Nielson, 2011, Carinoscapula sarcula (Nielson, 1992), Dicodia recurvata Nielson, 2011 (Coelidiini), and Plapigella elegans (Spångberg, 1878) (Teruliini). A new species of Coelidiini is also described: Daridna nielsoni sp. nov. from this reserve. A new junior synonym is also recognized: Vernobia johnsoni Nielson, 1979 equals Stalolidia amazonensis Barbosa & Takiya, 2017 syn. nov.